Impact of time and work:rest ratio matched sprint interval training programmes on performance: A randomised controlled trial - Lloyd Jones, M. C.; Morris, M. G.; Jakeman, J. R. (Journal of Science and Medicine in Sport, 2017)
Objectives: The aim of this study was to examine the effects of a short training intervention using two repeated sprint protocols matched for total sprint duration and work:rest ratio. Design: Randomised-controlled trial. Methods: Thirty physically active males were randomly allocated to one of two sprint training groups: a 6 s group, a 30 s group or a non-exercising control. The training groups were matched for work:rest ratio and total sprint time per session, and completed 6 training sessions over a 2-week period. Before and after the 2 week training period, participants completed a VO2max test and a 10 km time trial on a cycle ergometer. Results: Time trial performance increased significantly by 5.1% in 6 s (630 ± 115 s to 598 ± 92 s; p<0.05) and 6.2% in 30 s (579 ± 68 s to 543 ± 85 s; p <0.05) from baseline testing, but there was no significant change in the control group (p<0.05), and no significant difference between exercise groups (p < 0.05). The 6 s group increased peak power output by 9.0% (from 1092 ± 263 W to 1181 ± 248 W; p <0.05) from sprint session 1 to 6, and the 30 s group by 20.0% (1041 ± 161 W to 1237 ± 159 W; p <0.05). Conclusions: This study indicates that both 6 and 30 s bouts of repeated sprint exercise, matched for total sprint duration and W:R can improve athletic performance.